EFEKTIVITAS PROGRAM PELATIHAN MANAJEMEN KEWIRAUSAHAAN TERHADAP UMKM OLEH UPT BLP2TK SURABAYA - Aprilia, Vinka Dwi; Nafi’ah, Binti Azizatun (Gapenas Publisher, 2025)
Indonesia ranks 111th out of 189 countries with productivity figures that are far behind compared to neighboring countries. As an effort to increase labor productivity, the East Java Provincial Government through the Unit Pelayanan Teknis Balai Latihan Pengembangan Peningkatan Produktivitas Tenaga Kerja held a training program for Usaha Mikro, Kecil, dan Menengah (UMKM). This study aims to evaluate the effectiveness of the training program implemented by UPT BLP2TK in increasing the productivity of the UMKM workforce in East Java. This study uses a qualitative approach with descriptive analysis. Data were collected through interviews and observations on the implementation of the training program. The results of the study show that UPT BLP2TK has succeeded in identifying the need for industry skills and using competent instructors. However, limited resources and facilities cause the training to only accommodate a certain amount